Świadomość językowa i zainteresowania językoznawcze Adama Naruszewicza - Lewaszkiewicz, Tadeusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
Adam Naruszewicz, the eminent Enlightenment-era writer and father of modern Polish historiography was, like many authors before and after him, interested in linguistic issues. In his letters and in a preface to a translation of Tacitus’ works, he discussed the style of literary texts as well as the culture and the proper use of Polish among eighteenth-century educated classes. In his historical works, he advanced etymological ideas, both his own and those borrowed from other authors, and also mentioned the relationships between Indo-European and non-Indo-European languages.